Evidence for steric regulation of fibrinogen binding to staphylococcus aureus Fibronectin-binding Protein A ( FnBPA) - Stemberk,V; Jones,RPO; Moroz,O; Atkin,KE; Edwards,AM; Turkenburg,JP; Leech,AP; Massey,RC; Potts,JR (Journal of Biological Chemistry, 2014)
The adjacent fibrinogen (Fg)- and fibronectin (Fn)-binding sites on Fn-binding protein A (FnBPA), a cell surface protein from Staphylococcus aureus, are implicated in the initiation and persistence of infection. FnBPA contains a single Fg-binding site (that also binds elastin) and multiple Fn-binding sites. Here, we solved the structure of the N2N3 domains containing the Fg-binding site of FnBPA in the apo form and in complex with a Fg peptide. The Fg binding mechanism is similar to that of homologous bacterial proteins but without the requirement for “latch” strand residues. We show that the Fg-binding sites and the most N-terminal Fn-binding sites are nonoverlapping but in close proximity. Although Fg and a subdomain of Fn can form a ternary complex on an FnBPA protein construct containing a Fg-binding site and single Fn-binding site, binding of intact Fn appears to inhibit Fg binding, suggesting steric regulation. Given the concentrations of Fn and Fg in the plasma, this mechanism might result in targeting of S. aureus to fibrin-rich thrombi or elastin-rich tissues.